A Neurophysiological Investigation of Non-native Phoneme Perception by Dutch and German Listeners - Bien, Heidrun; Hanulíková, Adriana; Weber, Andrea; Zwitserlood, Pienie (Frontiers in Psychology, 2016)
The Mismatch Negativity (MMN) response has often been used to measure memory traces for phonological representations and to show effects of long-term native language (L1) experience on neural organization. We know little about whether phonological representations of non-native (L2) phonemes are modulated by experience with distinct non-native accents. We used MMN to examine effects of experience with L2-accented speech on auditory brain responses. Specifically, we tested whether it is long-term experience with language-specific L2 pronunciations or instead acoustic similarity between L2 speech sounds that modulates non-native phoneme perception. We registered MMN responses of Dutch and German proficient L2 speakers of English to the English interdental fricative /θ/ and compared it to its non-native pronunciations /s/ (typical pronunciation of /θ/ for German speakers) and /t/ (typical pronunciation of /θ/ for Dutch speakers). Dutch and German listeners heard the English pseudoword thond and its pronunciation deviants sond and tond. We computed the identity Mismatch Negativity (iMMN) by analyzing the difference in ERPs when the deviants were the frequent versus the infrequent stimulus for the respective group of L2 listeners. For both groups, tond and sond elicited mismatch effects of comparable size. Overall, the results suggest that experience with deviant pronunciations of L2 speech sounds in foreign-accented speech does not alter auditory memory traces. Instead, non-native phoneme perception seems to be modulated by acoustic similarity between speech sounds rather than by experience with typical L2 pronunciation patterns.